2018
DOI: 10.1111/imj.13998
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of translocated bacterial populations in patients with and without inflammatory bowel disease

Abstract: Metabolically active bacteria mirroring the individual's gut microbiome were commonly found in the lymph nodes of patients with IBD undergoing resection. An increase in lymph node alpha diversity is likely due to the larger drainage area. The presence of viable bacteria in non-IBD controls is also not unexpected given the underlying pathology in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…Parabacteroides in high abundance was found in immune-related diarrhea [39]. In addition, Alloprevotella ( Prevotellaceae family) is an anaerobic Gram-negative bacilli with the high relative abundance in patients with inflammatory bowel disease (IBD) [40]. Both Desulfovibrio and Acinetobacter ( Proteobacteria family) were associated with bloody diarrhea [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Parabacteroides in high abundance was found in immune-related diarrhea [39]. In addition, Alloprevotella ( Prevotellaceae family) is an anaerobic Gram-negative bacilli with the high relative abundance in patients with inflammatory bowel disease (IBD) [40]. Both Desulfovibrio and Acinetobacter ( Proteobacteria family) were associated with bloody diarrhea [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study include the small number of horses enrolled, which comprised a heterogeneous population with wide variation in age (between 1 and 21 years old) and breeds. Nevertheless, it has been shown that the microbiota of nine-month-old horses is very similar to adults [8] and that breed might not be a great factor of variability in the equine microbiota [9]. In addition, the treatment with antimicrobial drugs received by horses with colitis prior to sample collection likely induced changes in the microbiota [10].…”
Section: Comparison Between Healthy and Colitis Casesmentioning
confidence: 99%
“…Marked perturbation of the intestinal microbiota, particularly with respect to microbial diversity, has been documented in conditions such as inflammatory bowel disease, Crohn's disease and colitis in humans and in horses with undifferentiated colitis [7][8][9]. These observations suggest that in some cases of gastro-intestinal disorders, including horses, dysbiosis could play a role in the development of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these research have been based on bacterial-culture studies. But, more recently, molecular techniques have used bacterial RNA/DNA from blood and tissues as surrogate markers enabling a deeper analysis and the identification of unculturable bacteria 189 . As a case in point, a recent study confirmed a distinctly different microbial profile between CD and UC lymph nodes that could explain their different mechanisms of development and prognosis 190 .…”
Section: Disrupted Permeabilitymentioning
confidence: 99%